Individual, interpersonal and environmental correlates of sedentary behaviours in adults with intellectual disabilities. - Chusamer, K.; Melville, C. A.; McGarty, A. M. (Journal of Intellectual Disability Research, 2023)
Background: Sedentary behaviours have adverse health outcomes and adults with intellectual disabilities are at a higher risk of unhealthy lifestyle behaviours. The lack of knowledge relating to sedentary behaviours in adults with intellectual disabilities has impeded the development of effective interventions. This study aimed to investigate individual, interpersonal and environmental correlates that are associated with sedentary behaviours in adults with intellectual disabilities. Method: A secondary analysis of data from The UK Household Longitudinal Study (Understanding Society; collected 2011–2013) was conducted. Twenty‐two predictor variables were included in a stepwise logistic regression, with TV hours during weekdays (≤3 and >3 h/day) used as a proxy for sedentary behaviours. A sample of 266 adults, with mean age of 37.9 and range from 18 to 49 years old, with intellectual disabilities were identified. Because 63.9% were female, 62.4% had children and 28.2% were employed, the sample is likely to be most representative of more able adults with intellectual disabilities. Results: A significant interaction term between having children and neighbourhood status was found in the initial model so separate models for good and poor‐quality neighbourhoods are reported. Having children only had a significant effect to lower the odds of high TV time among participants living in good quality neighbourhoods (OR 0.10, 95% CI 0.03, 0.25). However, for people living in poor quality neighbourhoods it was better quality leisure services that was associated with lower odds of high TV time (OR 0.48, 95% CI 0.23, 0.90). Being employed only significantly reduced the odds of high TV time in the good quality neighbourhood model (OR 0.35, 95% CI 0.12, 0.78). These effects highlight the importance of environmental effects on lifestyle behaviours of adults with intellectual disabilities. Conclusions: Future research should aim to expand our understanding of environmental effects on the sedentary behaviours and other lifestyle behaviours of adults with intellectual disabilities.